2019
DOI: 10.3390/cancers11050602
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Selectively Impairs CAR-T Cells In Vitro

Abstract: Hypoxia is a major characteristic of the solid tumor microenvironment. To understand how chimeric antigen receptor-T cells (CAR-T cells) function in hypoxic conditions, we characterized CD19-specific and BCMA-specific human CAR-T cells generated in atmospheric (18% oxygen) and hypoxic (1% oxygen) culture for expansion, differentiation status, and CD4:CD8 ratio. CAR-T cells expanded to a much lower extent in 1% oxygen than in 18% oxygen. Hypoxic CAR-T cells also had a less differentiated phenotype and a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…These data support our hypothesis that the TSC population can be targeted using a DCLK1-specific CAR-T. Here, we report that, in collaboration with ProMab Inc., we have developed a novel CAR-T based on the DCLK1 ScFv containing a CD28 transmembrane and co-stimulatory domain and CD3ζ activation domain [39][40][41][42][43][44][45][46]. CAR-T cells generated using DCLK1 ScFv (CBT-511) demonstrated~20% CAR expression and significantly induced CRC cell cytotoxicity.…”
Section: Introductionsupporting
confidence: 73%
“…These data support our hypothesis that the TSC population can be targeted using a DCLK1-specific CAR-T. Here, we report that, in collaboration with ProMab Inc., we have developed a novel CAR-T based on the DCLK1 ScFv containing a CD28 transmembrane and co-stimulatory domain and CD3ζ activation domain [39][40][41][42][43][44][45][46]. CAR-T cells generated using DCLK1 ScFv (CBT-511) demonstrated~20% CAR expression and significantly induced CRC cell cytotoxicity.…”
Section: Introductionsupporting
confidence: 73%
“…Another study found the same effect, but attributed the slow growth at physiological DO to a build‐up of cAMP, which in turn, resulted in reduced T‐cell activation due to lymphocyte‐specific protein tyrosine kinase (Lck) inhibition (Larbi, Zelba, Goldeck, & Pawelec, 2010). In contrast, a study by Berahovich et al (2019) found no differences in the expansion of T cells and CD19 CAR‐T cells when cultured at physiological and atmospheric oxygen conditions.…”
Section: Discussionmentioning
confidence: 78%
“…The phenotypical distribution in this study was shown to be highest in CD8 T CM cells when the DO was controlled at 25% and the pH was set to 7.4. Thus far, most studies show no effect of the DO on the differentiation of T cells and CD19 CAR‐T cells (Atkuri et al, 2007; Berahovich et al, 2019). However, it is important to note that the majority of the referenced studies were not done under pH controlled or agitated conditions.…”
Section: Discussionmentioning
confidence: 99%
“…34 Furthermore, antigen-specific CAR-T cells that were mobilised into hypoxic tumour areas were more proliferative than CAR-T cells in normoxic areas, when evaluated in two in vivo models. 34,35 Berahovich et al 36 also explored the effects of hypoxia on CAR-T cells targeted against B-cell maturation antigen (BCMA) and CD19. They observed that hypoxia diminished the expansion of both CAR-and non-transduced T cells.…”
Section: Car-t Cells and Hypoxiamentioning
confidence: 99%